The Analysis of Work Motivation, Job Training and Non-Physical Work Environment on Employee Performance - Febrian, Wenny Desty; Alfiyanti, Selly (Siber Journal of Advanced Multidisciplinary, 2023)
This summary aims to describe the impact of motivation, job training, and non-physical work environment on employee performance. This research explores how these factors affect the productivity and work results of individuals in an organization. By looking at the relationship between motivation, training, and work environment that is not related to the physical, this study aims to provide a deeper understanding of the factors that can improve employee performance. In this study, researchers used the Quantitative Research Method with a population of 40 permanent employees at the XYZ Slimming Center Clinic, Branch West Jakarta, using the associative analysis method and SPSS 26 software.